Noncovariant gauges in canonical formalism - Burnel, Andre (Springer, 2017)
Chapter 1. Canonical Quantization for Constrained Systems. Chapter 2. Quantization of the Free Electromagnetic Field in General Class III Linear Gauges. Chapter 3. Quantization of the Free Electromagnetic Field in Class II Axial Gauges. Chapter 4. Gauge Fields in Interaction. Chapter 5. Perturbation Theory: Renormalization and All That. Chapter 6. Slavnov-Taylor Identities for Yang-Mills Theory. Chapter 7. Field Theory Without Infinities. Chapter 8. Gauges with a Singular C Matrix